Identitas dan Spirit Hidup ke Inspirasi Literasi Budaya: Studi Hikayat Hang Tuah - Mu’jizah Mu’jizah; Erlis Nur Mujiningsuh (Balai Bahasa Provinsi Bali, 2023)
Manuscripts in the Advancement Act are the second elements of the ten elements of culture. Among the manuscripts, one of them is the Hikayat Hang Tuah by the noble work which has become a Malay identity. This saga has a privilege in the hearts of its people. As a work of fiction, this saga traverses the world of facts and the existence of the character Hang Tuah is a role model for the Malay nation and his strong character as a hero becomes the spirit for the life of his people and becomes a source of inspiration in cultural literacy. This research aims to explore the features of Hikayat Hang Tuah as a work of historical literature which has become an encouragement so that the saga is transformed into various forms of transfers that increase cultural literacy. Qualitative methods are used in this research. From the results of the research it is known that this saga has proven itself to be a noble work which from the 18th to the 21st century has always been appreciated and used as research material by researchers from various countries. The myths and historical elements of Hang Tuah's character become an encouragement that never goes away in the supporting community who regard Hang Tuah's figure as not only a cultural hero, but also a hero in history. This feature shows that the saga is manifested through imagination and a factual setting with historical events. This community trust is a force in increasing and developing cultural literacy. AbstrakManuskrip dalam Undang-Undang Pemajuan menjadi unsur kedua dari sepuluh unsur budaya. Di antara manuskrip itu salah satunya Hikayat Hang Tuah karya adiluhung yang menjadi identitas Melayu. Hikayat ini mempunyai keistimewaan di dalam hati masyarakatnya. Sebagai karya fiksi, hikayat ini melintasi dunia fakta dan keberadaan tokoh Hang Tuah menjadi teladan bangsa Melayu dan karakternya yang kuat sebagai hero menjadi spirit bagi kehidupan masyarakatnya dan menjadi sumber inspirasi dalam literasi budaya. Penelitian ini bertujuan menggali keistimewaan Hikayat Hang Tuah sebagai karya sastra sejarah yang telah menjadi penyemangat sehingga hikayat itu bertransformasi ke dalam bentuk aneka alih wahana yang meningkatkan literasi budaya. Metode kualitatif digunakan dalam penelitian ini. Dari hasil penelitian diketahui bahwa hikayat ini membuktikan dirinya sebagai karya adiluhung yang sejak abad ke-18 hingga abad ke-21 selalu diapresiasi dan dijadikan bahan penelitian oleh peneliti berbagai negara. Mitos dan unsur sejarah tokoh Hang Tuah menjadi penyemangat yang tak pernah padam di dalam masyarakat pendukungnya yang menganggap tokoh Hang Tuah bukan hanya sebagai pahlawan budaya, melainkan pahlawan dalam sejarah. Keistimewaan itu memperlihatkan bahwa hikayat diejawantah melalui imajinasi dan latar faktual dengan peristiwa sejarah. Kepercayaan masyarakat ini menjadi kekuatan dalam meningkatkan dan pengembangan literasi budaya.